Analytical Analysis of Fractional-Order Newell-Whitehead-Segel Equation: A Modified Homotopy Perturbation Transform Method. (10th June 2022) - Iqbal, Naveed; Albalahi, Abeer M.; Abdo, Mohammed S.; Mohammed, Wael W.
Abstract : This paper has applied a hybrid method called the homotopy perturbation transformation technique to solve fractional-order Newell-Whitehead-Segel equations. First, we used the Yang transformation to the given problem, and then, the homotopy perturbation technique was implemented to complete the procedure of the suggested method. The proposed method is simplified and requires a small calculation to achieve the solution to the targeted problem. Moreover, the derived results are in close contact with the exact results of the given models. Three examples are solved to confirm and show the feasibility of the present scenario. The findings obtained from the proposed procedure have also been in excellent alignment with other technique outcomes. It is shown that the proposed approach is effective, consistent, and straightforward to apply to various relevant problems in engineering and science.